2020
DOI: 10.1177/1071100720938049
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineralization Changes in the Subchondral Bone of the Medial Gutter in Chronic Lateral Ankle Instability

Abstract: Background: Chronic ankle instability (CAI) induces osteoarthritis (OA) by inflicting abnormal stresses on the medial gutter. It is important to detect early OA change and to explore factors likely to induce the OA. The purpose of this study was to evaluate subchondral bone change in the medial gutter of CAI using computed tomography (CT) scans. Methods: Thirty-five ankles with CAI (CAI group) and 35 ankles without CAI (control group) were included. The region of interest (ROI) in the subchondral bone of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…showed that ankles with repetitive ankle sprains exhibited greater internal rotation of the talus from heel contact to 60% of the stance phase [25]. Our previous report showed higher HU values at the medial gutter in patients with CLAI than in those without CLAI [9]. The stress distribution on the medial gutter due to internal rotation, in addition to the increasing inversion angle of the talus, may lead to a varus type OA.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…showed that ankles with repetitive ankle sprains exhibited greater internal rotation of the talus from heel contact to 60% of the stance phase [25]. Our previous report showed higher HU values at the medial gutter in patients with CLAI than in those without CLAI [9]. The stress distribution on the medial gutter due to internal rotation, in addition to the increasing inversion angle of the talus, may lead to a varus type OA.…”
Section: Discussionmentioning
confidence: 86%
“…The HU is defined based on a scale created by the linear transformation of the original linear attenuation coefficient measurement into one where the radiodensity of distilled water at standard temperature and pressure is set at 0 and that of air at − 1000 [5,6]. Using this technique, small changes in the subchondral bone can be detected, and several studies have reported the usefulness of this technique for evaluation stress distributions in several joints [7][8][9][10]. The measurement of the HU unit on CT images enables us to understand the stress distribution pattern in talocrural and subtalar joints in patients with CLAI.…”
Section: Introductionmentioning
confidence: 99%
“…The CT images of the ankle joint can aid in the evaluation of articular cartilage injury and bone mineralization changes in the subchondral bone. 24,25 Therefore, in addition to the conventional imaging examination such as stress radiograph and MRI, degeneration of the deltoid ligament should be evaluated on CT images to utilize HU measurements for the diagnosis of RAI in CAI patients. Further studies with larger sample sizes should be required to determine the cut-off value of HU measurements in deltoid ligament degradation for diagnosis of RAI.…”
Section: Discussionmentioning
confidence: 99%
“…Low HU values of the dPTL might indicate a perceived risk of developing OA because CAI patients with initial OA changes presented low HU values of the dPTL compared to CAI patients without radiographic early OA changes, regardless of whether their MRI findings of dPTL injury were negative or positive. The CT images of the ankle joint can aid in the evaluation of articular cartilage injury and bone mineralization changes in the subchondral bone 24,25. Therefore, in addition to the conventional imaging examination such as stress radiograph and MRI, degeneration of the deltoid ligament should be evaluated on CT images to utilize HU measurements for the diagnosis of RAI in CAI patients.…”
mentioning
confidence: 99%
“…HU values are standardized linear attenuation coefficients for tissue [ 13 ]. Studies have reported the use of HU measurements to determine the subchondral bone density, in which specific stress distributional patterns of the medial gutter in the talocrural joint and the lateral aspect of the subtalar joints were studied in patients with chronic lateral ankle instability [ 14 , 15 ]. Previous studies on bone density analysis have revealed that the distal-dorsolateral area is the densest portion of the medial cuneiform [ 16 ].…”
Section: Introductionmentioning
confidence: 99%